Perspective of sustainable mode in Peru - Tinoco Gómez, Óscar (2009)
The concept of sustainability has penetrated different levels of European industry and textile fashion due to three reasons: 1) the pressure of NGOs, unions and environmentalists in general, who demand products and clean production and sensitive to Fair Trade, 2 ) the environmental impacts of the traditional textile industry, whose consequences are not adequately treated, generating pollution and 3) increasing environmental awareness level of the planet as a whole. Because of these reasons and pressure from the expanding Chinese textiles, European countries are developing niche-oriented “green” products, giving priority to natural fibers, especially organic cotton. In Peru, sectors of the textile and fashion industry are strongly oriented to work sustainable fashion, which creates opportunities both domestically and in the category of exports.